Highly selective CO2vs. N2 adsorption in the cavity of a molecular coordination cage. Issue 31 (5th April 2017) - Wright, James S.; Metherell, Alexander J.; Cullen, William M.; Piper, Jerico R.; Dawson, Robert; Ward, Michael D.
Abstract : A cubic coordination cage shows high selectivity for CO2 vs. N2 uptake in the cage cavity, despite the bulk material being non-porous. Abstract : Two M8 L12 cubic coordination cages, as desolvated crystalline powders, preferentially adsorb CO2 over N2 with ideal selectivity CO2 /N2 constants of 49 and 30 at 298 K. A binding site for CO2 is suggested by crystallographic location of CS2 within the cage cavity at an electropositive hydrogen-bond donor site, potentially explaining the high CO2 /N2 selectivity compared to other materials with this level of porosity.